Relationship of cervical ectopy to chlamydia infection in young women. Issue 2 (1st April 2006) - Lee, Vincent; Foley, Elizabeth; Tobin, Jean M
Abstract : Objective: Genital Chlamydia trachomatis infection is the most common bacterial sexually transmitted infection (STI) in the UK. Behaviours including multiple sex partners and inconsistent condom use, and biological factors such as cervical ectopy, may increase susceptibility to STIs. Cervical ectopy is thought to increase risk of chlamydia infection by exposing columnar epithelium to a potential infectious inoculum. This study aimed to determine whether chlamydia was more prevalent in young women with cervical ectopy. Methods: Clinical notes of women aged 16–24 years attending the Portsmouth Genitourinary Medicine Clinic for an STI screen during the period May–July 2003 were reviewed retrospectively. Information collected included the presence or absence of cervical ectopy, smoking habits, methods of contraception, number of sexual partners in the previous 3 months, and previous STIs. Chlamydia infection was diagnosed by using strand displacement amplification on cervical swabs. Results: A total of 231 women were included in the study. The mean age was 19.8 years. Evidence of cervical ectopy was found in 107 women. Chlamydial infection was detected in 37.4% (40/107) of those women with cervical ectopy and 21.8% (27/124) in those without cervical ectopy. This difference was statistically significant ( p = 0.009). The significance remained even when accounting for confounding variables. Conclusions: Cervical ectopy is a common physiological process in young women. Recognition of cervical ectopy should alert the clinician to the possibility of a genital chlamydia infection. Opportunistic screening for chlamydia in young people should be offered to reduce the prevalence of infection and its sequelae.